NARZIBMUS: EINE THEORIE DER PSYCHOANALYTISCHEN BEHANDLUNG NARZIBTISCHER PERSONLICHKEITSSTORUNGEN - Kohut, Heinz (SUHRKAMP TASCHENBUCK WISSENSCHAFT;, 1976)
TRADUCCION DE: THE ANALYSIS OF THE SELF. A SYSTEMATIC APPROACH TO THE PSYCHOANALYTIC TREATMENT OF NARCISSISTIC PERSONALITY DISORDER